Comparison of the Effectiveness of Hatha Yoga and Mindfulness Exercises on Generalized Anxiety and Existential Anxiety in Young Men in Kermanshah - Mahidashti, Farhad; Mihandoost, Zeinab; Soleimannejad, Homeira (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The aim of the present study was to compare the effectiveness of Hatha Yoga exercises and mindfulness-based therapy on generalized anxiety and existential anxiety in physically active and inactive men aged 30 to 50 years in the city of Kermanshah. Methods and Materials: This study employed a quasi-experimental design with a pre-test, post-test, and a 2-month follow-up period, along with a control group. The statistical population included all men aged 30 to 50 years who had enrolled in yoga classes in Kermanshah during the winter of 2023. The research sample consisted of 45 individuals selected through convenience sampling and randomly assigned to experimental groups (Hatha Yoga exercises and mindfulness-based therapy) and a control group. Participants completed the Generalized Anxiety Disorder questionnaire by Spitzer et al. (2006) and the Existential Anxiety questionnaire by Lawrence Good (1974) during the pre-test, post-test, and follow-up phases. Participants in the Hatha Yoga and mindfulness-based therapy groups underwent eight 90-minute training sessions, conducted once a week. Data were analyzed using SPSS version 27. Findings: The results indicated that both Hatha Yoga exercises and mindfulness-based therapy led to improvements in generalized anxiety and existential anxiety in physically active and inactive men aged 30 to 50 years in Kermanshah during the post-test and follow-up phases (P < 0.05). Furthermore, no significant difference was found between Hatha Yoga exercises and mindfulness-based therapy (P > 0.001). Conclusion: Based on the findings, it can be concluded that both Hatha Yoga exercises and mindfulness-based therapy are effective approaches in improving generalized anxiety and existential anxiety.